A new Malaysian quality of life index based on fuzzy sets and hierarchical needs - Abdullah, Mohd Lazim; Md. Tap, Abu Osman (Springer, 2009)
The Malaysian Quality of Life Index (MQLI) released by the Economic Planning Unit (EPU), has led authors to search for alternative method of expressing this index. One of the limitations in MQLI computations is the failure to recognise unequal weights for each accounted component. This paper offers a new way of expressing the quality of life index using a mathematical modelling based on fuzzy sets theory and the proposed weights based on Maslow’s theory of hierarchical human needs. The indices of 11 components that were used to compute MQLI, again be gathered as a basis in expressing a new Malaysian Fuzzy Quality of Life Index (MFQLI). The new indices for each component yielded through a normalisation process prior weighting and aggregation to compose a new MFQLI. It was found that a fuzzy sets approach with the inclusion of weights based on human needs yielded a better index of quality of life than the MQLI.